Radiation Dose Reduction for Computed Tomography Localizer Radiography Using an Ag Additional Filter. Issue 1 (January 2021) - Nomura, Keiichi; Fujii, Keisuke; Goto, Takahiro; Tsukagoshi, Shinsuke; Ota, Hiroyuki; Iwabuchi, Yuto; Suzuki, Hidenobu; Muramatsu, Yoshihisa; Kobayashi, Tatsushi
Abstract : Objective: This study aimed to assess the potential of an Ag additional filter attached to the bow tie filter of a computed tomography (CT) scanner to reduce the radiation dose in CT localizer radiography. Methods: Radiation doses in CT localizer radiography with Cu and Ag additional filters were evaluated based on dose measurements and Monte Carlo simulations. Image quality evaluations of an adult torso phantom were performed, and the automatic exposure control performance was evaluated in terms of the water-equivalent thickness estimated from CT localizer radiographs. Results: With the Ag additional filter, effective doses were approximately 72% to 75% lower than those with the Cu additional filter. The image quality and water-equivalent thickness with the Ag additional filter were similar to those with the Cu additional filter. Conclusions: The Ag additional filter helped significantly reduce radiation doses in CT localizer radiography while maintaining image quality and performance.